A norma-padrão Europeia e a mudança linguística na Escola Moçambicana - Timbane, Alexandre António [UNESP]; Berlinck, Rosane de Andrade [UNESP] (My University, 2012)
In Mozambique, the portuguese language is considered the official language, second language, national language and competes with more than twenty Bantu languages spoken by the majority of population. The standard norm lose away their floor to the Mozambican Portuguese which carries own characteristics pertaining to the sociolinguistic context of the country. Schools attempt their best, but they cannot teach the European standard due the multilingual and Portuguese contact with African languages, a fact that is reflected in the media and in the literature through their oral and written forms. These difficulties result in high rates of failures due to problems encountered in using the European standard by teachers and writers who prepare the school books. This research suggests the standardization of the Mozambican variant as well as the preparation of dictionaries and grammars illustrating the sociolinguistic reality of Mozambique in order to improve the quality of education. It also emphasizes the need for a self-esteem spirit on Mozambicans in general as a conduit to eliminate the soaring bias that Mozambicans can not speak portuguese language

Em Moçambique, a língua portuguesa é considerada língua oficial, língua segunda, língua nacional e concorre com mais de vinte línguas bantu faladas pela maioria da população. A norma-padrão perde espaço dando lugar ao português moçambicano que tem caraterísticas próprias do contexto sociolinguístico do país. A escola se esforça, mas não consegue ensinar essa norma européia devido ao multilinguismo e o contato do português com as línguas africanas, fato que se reflete nos mídias e na literatura oral e escrita. Esta dificuldade resulta em altos índices de reprovações causados pela dificuldade do uso do padrão-europeu por parte de professores e dos escritores que elaboram os livros escolares. Nesta pesquisa sugere-se a padronização da variante moçambicana, bem como a elaboração de dicionários e de gramáticas que ilustrem a realidade sociolinguística de Moçambique para a melhoria da qualidade de ensino e também para a autoestima dos moçambicanos em geral, eliminado assim o preconceito de que os moçambicanos não sabem falar português.
Keywords: Standard-norm; Change; Mozambican Portuguese; Norma-padrão; Mudança; Português moçambicano